FILM A MAN SPACE: (FILM TANPA PEREMPUAN) - Afandi, Haekal Ridho; Ali, Matius (Seni Media Rekam ISI Surakarta, 2017)
A Man Space is a short fiction film that adopts masculine and feminism in a human body, which tells of a family consists of a father and three sons without a woman in the house. All was gone smoothly before there is occurs a problem where the father wanted to replace their mother figure. The film’s problems are not only the father wants to get married again, but also the problems that arise in the community. A man was called as a man because of what? The third child’s question to his father because he was the last son and still searching for his identity while his old brothers already have different characters each other though in the one house and no one could finish this problems only respond with a man way. Without a woman, a man can do what he wants.Keywords: A Man Space, without woman, masculine, and feminine